Transvenous Coil Embolization for Dural Arteriovenous Fistula of the Anterior Condylar Confluence – a Case Report - Bohara, Manoj; Teranishi, Kosuke; Yatomi, Kenji; Fujii, Takashi; Kitamura, Takayuki; Yamamoto, Munetaka; Oishi, Hidenori (Nepal Journal of Neuroscience, 2018)
Dural arteriovenous fistula (DAVF) of the anterior condylar confluence (ACC) is a rare entity accounting for about 3.6% of all DAVFs. We report on a 63-year-old male patient who presented with pulsatile tinnitus. Angiography revealed a DAVF supplied mainly by neuromeningeal branches of bilateral ascending pharyngeal arteries and draining into the ACC. Transvenous transjugular coil embolization was performed resulting in complete obliteration of the fistula and resolution of the symptoms. Due to the complexity of this venous structure at the skull base, detailed angiographic study is crucial for proper therapeutic planning and management of the patient. We here discuss the clinico-radiological features and various treatment modalities of the ACC DAVF. Nepal Journal of Neuroscience, Volume 15, Number 2, 2018, page: 41-44